Effectiveness Of Banana Nangka (Musa Paradisiaca Linn) Skin as A Natural Coagulant In Reducing Turbidity Of River Water - Nurhaliza, Nafa Berliana; Juanda, Juanda; Hamzani, Sulaiman (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Jackfruit Banana peel is one type of plant that can be used to reduce the turbidity of river water. Jackfruit banana peel contains cellulose, hemicellulose and lignin. Cellulose's potential as an adsorbent is substantial. This study aims to determine the effectiveness of jackfruit banana peel variations in dose and contact time as a natural coagulant in reducing river water turbidity. This type of research is experimental, the research uses a pretest-posttest design with control group design, with 5 treatments with 3 treatments. Data analysis used the Two-Way Anova statistical test to determine the difference in each treatment to the resulting decrease in turbidity with = 0.05. The results of the analysis showed that the p value was 0.000 < = 0.05, which means that there was a difference in the decrease in dosage variation and contact time of jackfruit banana peel powder (Musa paradisiaca linn). Before processing river water banana and jackfruit peel powder, the average yield was 9.29 NTU. Optimum dose 1.2 grams and presentation of 71.48% decrease in turbidity. Further researchers can use jackfruit banana peels in overcoming the pH of the air after adding banana peel powder and there are further researchers to utilize banana peels in wastewater treatment.